Analisis Peranan Kelompok KKN 154 Dalam Membantu Peningkatan Umkm Di Desa Ulumahuam Kecamatan Silangkitang Kabupaten Labuhan Batu Selatan - Yani Lubis; Yungki Akbar; Cindy Triningsih; Febri Shaleh Siregar; Dewi Dokate Manalu (UNIVED Press, 2023)
Real Work Lecture (KKN) which was held by the KKN-154 group in Ulumahuam Village, Silangkitang District, Labuhan Batu Selatan Regency which was held for 30 days, namely 18 July-18 August 2022. While carrying out KKN in Ulumahuam Village, Silangkitang District, Labuhan Batu Selatan Regency, they were welcomed both by the community and the community also participate in activities that the KKN team has planned. The purpose of this study was to analyze how the role of the 154 KKN group in helping to increase MSMEs in Ulumahuam Village, Silangkitang District, Labuhan Batu Selatan Regency. This study uses qualitative research methods, with interview and observation data collection techniques. This study resulted that the KKN-154 group played a good and influential role for the village community in improving the economy and empowering the community. In this case, the KKN-154 group, Ulumahuam Village, Silangkitang District, Labuhan Batu Selatan Regency has a good role in helping the community in increasing MSMEs. For example, in empowering the community to make sunlight washing soap.